Interstate cooperation : compacts and administrative agreements - Zimmerman, Joseph Francis, 1928- (Praeger, 2002)
This text places in perspective the important roles played by interstate compacts and interstate administrative agreements in the governance systems of the US. Compacts are identified and classified by type, and particular emphasis is placed on federal governmental promotion of compacts.